Influence Self-leadership And Self-efficacy on Entrepreneurial Performance: The Mediating Role of Entrepreneurial Commitment in the Car Repair Industry of Badung Regency - Sanjaya, Gede Delin; Rahyuda, Agoes Ganesha (Eduvest - Journal of Universal Studies, 2025)
A productive and competent entrepreneur is needed in a business. The entrepreneur's performance plays an important role in the business's success. The existence of self-characteristics, such as self-leadership, self-efficacy, and good entrepreneurial commitment, will build the entrepreneur's performance more optimally. This study aims to analyse the role of entrepreneurial commitment in mediating the influence of self-leadership and self-efficacy on entrepreneurial performance in the Badung Regency Car Repair Industry. Sampling in this study used the saturated sample method, involving 42 entrepreneurs in the Badung Regency car repair industry. Data was collected using a questionnaire. The data analysis method used was Structural Equation Modelling (SEM) based on Partial Least Squares (PLS) with SmartPLS 4.1 software. The research results show that self-leadership and entrepreneurial commitment positively affect entrepreneurial performance. Self-efficacy does not affect entrepreneurial performance. Self-leadership and self-efficacy have a positive effect on entrepreneurial commitment. Entrepreneurial commitment partially mediates the influence of self-leadership on entrepreneurial performance and fully mediates the influence of self-efficacy on entrepreneurial performance. This study concludes that with strong self-leadership and self-efficacy, entrepreneurs will be able to increase their entrepreneurial commitment, ultimately improving their performance. Therefore, entrepreneurs need to maintain and develop their self-characteristics and entrepreneurial commitment to improve their performance sustainably.